Breed effects of cow's sire and service sire on reproduction of crossbred dams and preweaning performance of their calves - lsea, W.; Olson, T. A. (Revista Científica de la Facultad de Ciencias Veterinarias, 2010)
Reproductive traits and preweaning growth of progeny from crossbred cows sired by Braford, Simbrah, Senepol and Simmental bulls and from Zebu-crossbred cows were compared to Brahman x Angus F1 cows. Al1 dams were bred to Brangus and Limousin since 1989 to 1994 varying in age from two to five years and over. The cattle were handled in accord with the usual Beef Research Unit management system where the experiment was conducted, located in North-Central Florida near Gainesville and under subtropical climate. The cattle were grazed on Bahiagrass pastures as well as fed a corn-silage soybean meal based diet. The statistical model fitted effects of calving year CY, dam age DA, sire breed of calf SBC, sire breed of dam SED, calf sex, calf age used as a covariate and the random effect of cow within SED. Data analyses were conducted using PROC GLM of SAS (24). Results from the evaluation of the maternal performance of crossbred dams indicated, firstly, that both cow and CY significantly influenced variation in reproduction as well as SED affected (P Ë‚ .05) pregnancy rate and calf survival to weaning. Secondly, regarding to the calf traits, al1 the effects significantly influenced the preweaning growth, except for SBC, CY and DA which did not affect (P > .20) birth wi of the calf. Brahman x Angus F1 cows performed the greatest for survival rate, 205-d wt and ADG; however, Simmental-sired crossbred dams were the highest (P Ë‚ .05) for calving, pregnancy and weaning rates per cow exposed to breeding. 60th Simmental- and Brahman-sired cows performed the same on the kg of calf weaned per cow exposed. Contrasts of Brahman-derivative (Brangus, Braford, Simbrah) sired cows exceeded (P Ë‚ .05) Bos taurus (Senepol, Simmental) sired cows for weaning rate (2%), weaning wt (20 kg). 205-d wt (15 kg), ADG (100 g/d); nevertheless, the opposite ocurred for calving (-33%), pregnancy (-44%) and survival (-32%) rates. This study suggests that there is evidence of higher maternal heterosis in calf growth than in reproductive characters, and also that breed selection is important when planning a continuous crossbreeding program to obtain maximum benefit from heterosis in Florida's cow-calf operations.